The Effect of Cork Fish (Channa striata) Extract on Perineal Wound in the Work Area of Walantaka Community Health Center in 2020 - Afriani, Nur; Indrayani, Triana; Carolin, Bunga Tiara (Universitas STRADA Indonesia, 2020)
Perineal wound occurs because of a tear in birth canal or because of an episiotomy during childbirth. Slow healing of perineal wound can increase the risk of infection, so nutritional intake is needed, especially proteins that support new cell growth. This study utilized a Quasi-Experimental method with type of posstest-only control group design. Population in this study was postpartum mothers, with a total sample of 40 people taken by total sampling technique. Results showed that mean value in control group was 6.9, while mean value in intervention group was 4.8. Additionally, Mann-Whitney U test results obtained p = 0.000. In conclusion, there is an average difference in perineal wound healing between intervention and control groups, and there is an effect of giving cork fish extract (Channa striata) to perineal wound. It is expected that researchers can share this knowledge with postpartum mothers so that they consume cork fish extract as a therapy to accelerate perineal wound healing